PHYSICAL CHARACTERISTICS AND MAGNETIC PROPERTIES OF BAFE12O19/SRTIO3 BASED COMPOSITES DERIVED FROM MECHANICAL ALLOYING (Universitas Negeri Semarang, 2016)
Barium hexaferrite and strontium titanate are well established permanent magnet and piezoelectric materials which are technologically and scientifically attractive due to their potential for various applications in the field of magnetic electronics functional materials. However, the material properties for both require a careful control of grain structure as well as microstructure design to meet a specific application. In this work, we report some results of materials characterization especially particles and grains which were promoted during mechanical milling of a BaFe12O19/SrTiO3 composite system. These are including mean particle size characterization by Particle Size Analyzer and mean grain size determination by means of line broadenning analysis employing a step scanning counting in XRD apparatus for composite powders at various milling time up to 60 hours. It was found that the particle size of composite powders initially increased due to laminated layers formation of a composite and then decreased to an asymptotic value of 8 μm as the milling time extended even to a relatively longer time. However, based on results of line broadening analysis the mean grain size of the particles was found in the nanometer scale. We thus believed that mechanical blending and milling of mixture components for the composite materials has promoted heterogeneous nucleation and only after successive sintering at 1100 oC the milled powder transformed into particles of nanograin. In thireport, microstructure as well as magnetic properties for the composite is also briefly discussed.